The group A streptococcal collagen‐like protein‐1, Scl1, mediates biofilm formation by targeting the extra domain A‐containing variant of cellular fibronectin expressed in wounded tissue. Issue 3 (26th December 2012) - Oliver‐Kozup, Heaven; Martin, Karen H.; Schwegler‐Berry, Diane; Green, Brett J.; Betts, Courtney; Shinde, Arti V.; Van De Water, Livingston; Lukomski, Slawomir
Summary Wounds are known to serve as portals of entry for group A Streptococcus (GAS). Subsequent tissue colonization is mediated by interactions between GAS surface proteins and host extracellular matrix components. We recently reported that the streptococcal collagen‐like protein‐1, Scl1, selectively binds the cellular form of fibronectin (cFn) and also contributes to GAS biofilm formation on abiotic surfaces. One structural feature of cFn, which is predominantly expressed in response to tissue injury, is the presence of a spliced variant containing extra domain A (EDA/EIIIA). We now report that GAS biofilm formation is mediated by the Scl1 interaction with EDA‐containing cFn. Recombinant Scl1 proteins that bound cFn also bound recombinant EDA within the C‐C' loop region recognized by the α9β1 integrin. The extracellular 2‐D matrix derived from human dermal fibroblasts supports GAS adherence and biofilm formation. Altogether, this work identifies and characterizes a novel molecular mechanism by which GAS utilizes Scl1 to specifically target an extracellular matrix component that is predominantly expressed at the site of injury in order to secure host tissue colonization.